Remedy for work stress: the impact and mechanism of ethical leadership - Zhou, Hao; Jin, Maozhu; Ma, Qian (Central European Journal of Public Health, 2015)
AIM: Ethical leadership was characterized by integrity, honesty and trustworthiness. The purpose of this study was to investigate whether and how ethical leadership relates to employees' work stress, specifically the mediating role of leader-member exchange (LMX), which referred to the dyadic exchange relationships between supervisors and subordinates within the workplace. METHODS: Cross-sectional data for ethical leadership, LMX, perception of work stress, and control variables were collected through the questionnaire that included 47 multiple-choice questions and 3 open-ended questions. Double-blind design was adopted in this study. Hypotheses were tested by hierarchical regression analysis. RESULTS: 203 first-line technical support employees from a communications enterprise participated in this study (return ratio 98.5%). Of the respondents, 58.6% were male, average age was 35.24 years, average years in the company and in current position were 13.67 years and 11.12 years, respectively. Results revealed that the subjective evaluation of supervisors' ethical leadership was negatively related to employees' perception of work stress (β=-0.24, p<0.001), and this relationship was completely mediated by LMX. CONCLUSIONS: Through establishing high-quality LMX, ethical leadership played an important role in relieving employees' perception of work stress.
Keywords: dospělí; pracovní uspokojení; průzkumy a dotazníky; Female; Adult; ženské pohlaví; China; psychický stres; průřezové studie; Surveys and Questionnaires; vůdcovství; interpersonální vztahy; Leadership; lidé; dvojitá slepá metoda; Ethics; etika; nemoci z povolání; Cross-Sectional Studies; Double-Blind Method; Male; Job Satisfaction; Čína; Occupational Diseases; Interpersonal Relations; mužské pohlaví; Stress, Psychological; Humans